Computer simulation of mechanisms to reduce the metabolic costs of running while taking into account the individual characteristics of the athlete - Shestakov, M; Korchagin, A. (Technology in Sports - Recent Advances, New Perspectives and Application, 2023)
Previous research demonstrates the relationship between the biomechanical characteristics of running and running economics (RE). An increase in results in cycle-based sports is connected with the improvement of motion biomechanics tailored for individual athletes. The purpose of the chapter is to conduct a computer simulation of the use of biomechanical mechanisms of the lower limb muscles during running, leading to a decrease in metabolic costs. Eight biathletes took part in the experiments: all from the top 30 world ratings at the time of the study. For experiments, we used a Qualisys motion capture system, a power plate (Tredmetrix) mounted on a treadmill, a Biodex-3 complex, and a Metamax-3 gas analyzer (Cortex). OpenSim software allows modeling based on collected experimental data. This study describes the methodology of an individual approach to the process of training elite-level athletes based on computer modeling. In particular, we studied the possibility of reducing metabolic costs when working above the anaerobic limit, that is, similar to the actual competitive speed for biathlon and cross-country skiing. The results of the model experiment clearly demonstrated that one of the potential ways to reduce metabolic costs during running is the individualization of the use of biomechanical mechanisms for performing repulsion in a running step.